1998
DOI: 10.1007/s002689900453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single‐voided Urine Metanephrine and Normetanephrine Assay for Diagnosing Pheochromocytoma

Abstract: Urinary catecholamines (CAs) and their metabolites are usually measured during the process of diagnosing pheochromocytoma (pheo), but a 24-hour urine collection is not convenient for outpatients. Since 1987 we have utilized "spot" urine metanephrine (MN) and normetanephrine (NMN) assays for management of patients with pheo or adrenal incidentaloma. MN and NMN were measured by radioimmunoassay in 82 patients with surgically proved pheo and 15 patients with incidentaloma. In 10 patients with pheo, MN and NMN wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…49,148 Whilst random urine samples have also been proposed for diagnosing phaeochromocytoma in adults, 149,150 the measurement of free catecholamines and total metadrenalines has generally been undertaken using 24-h urine samples since this represents an integrated index of catecholamine excretion over the extended collection period. However, the problems associated with completeness of 24-h urine collections has led to proposals for alternative collection strategies involving fractional timed urine collections or volume correction by expressing results as ratios to creatinine.…”
Section: Pre-analytical Considerations Type Of Urine Specimenmentioning
confidence: 99%
“…49,148 Whilst random urine samples have also been proposed for diagnosing phaeochromocytoma in adults, 149,150 the measurement of free catecholamines and total metadrenalines has generally been undertaken using 24-h urine samples since this represents an integrated index of catecholamine excretion over the extended collection period. However, the problems associated with completeness of 24-h urine collections has led to proposals for alternative collection strategies involving fractional timed urine collections or volume correction by expressing results as ratios to creatinine.…”
Section: Pre-analytical Considerations Type Of Urine Specimenmentioning
confidence: 99%
“…The screening examinations depended on the institutions where the patients were assessed, but determination of the absence of PHEO was based on measurements of urinary metanephrine and normetanephrine per mg creatinine levels as a minimum (13). To calculate the penetrance of PHEO in MEN2, the index cases for each family were excluded from the calculation.…”
Section: Clinical Datamentioning
confidence: 99%
“…In addition, Perry et al reported metanephrine and normetanephrine diagnostic cut-off values for pheochromocytoma of 302 µg/d and 733 µg/d, respectively, as measured by tandem mass spectrometry [17]. However, there are limited data to suggest optimal cut-off values in Asian patients, and whether different cut-off values are necessary according to sex has not been evaluated [18]. Here, we aimed to establish cut-off values for urinary fractionated metanephrines for the diagnosis of pheochromocytoma in Korean patients and to determine cut-off values according to sex.…”
Section: Biochemical Methodsmentioning
confidence: 99%